KAJIAN PENERAPAN ARSITEKTUR ISLAM PADA PAUD UMMUSABRI DI KOTA KENDARI - Mulyani, Indah Tri; Nurdin, Takdir; Firman, La Ode; Ahmad, Oyon; Jurumai, La Pande (Institut Teknologi dan Bisnis Ahmad Dahlan, 2024)
The study on the Implementation of Islamic Architecture at Ummusabri Early Childhood Education Center (PAUD) in Kendari City is an in-depth analysis of the architectural design of this early childhood education institution. The research aims to comprehend the implementation of Islamic architectural principles in the structure of PAUD Ummusabri, with a focus on elements such as lighting, geometric patterns, integration with nature, and the influence of traditional Islamic architecture. The research methodology involves on-site observations, documentation studies, and interviews with architects or relevant stakeholders. The findings are anticipated to provide profound insights into how Islamic architectural design is applied in pre-school educational institutions, particularly in PAUD Ummusabri.